Haemogram and hormonal profile of WAD buck treated with leaf ethanol extract of spondias mombin (2017)
Twelve post pubertal West African Dwarf (WAD) bucks of average age of 1.8 ± 0.19 years and average weight of 8.76 ± 0.72 kg were experimentally treated orally with 800mg/kgBW of ethanol extract of Spondias mombin. Experiment was carried out in the month of August at Abeokuta, South West Nigeria with temperature range of 24oC and 33oC on Latitude 07o 10’N and Longitude 03o 2’E. The goats had well-formed pendulous scrotum with well descended free bilateral testicles. The goats were kept in a standard goat pen and fed with fresh green centrosema leaves in the morning and commercially prepared ration in the evening. Water was served ad libitum. Pre-treatment haematological and hormonal profiling after aseptical collection of blood from the bucks was followed with 14 days of oral treatment with ethanol extract of Spondias mombin at the dosage rate of 800mg/kg BW. Post-treatment haematological and hormonal studies followed after. The hormones assayed were follicle stimulating hormone (FSH), luteinising hormone (LH), testosterone, progesterone, estrogen and prolactin. The haemogram revealed significantly (p < 0.05) higher PCV (24.33±0.6 %) in pre-treatment compared to 19.92± 1.1 % recorded for post-treatment. However, both were lower in values than normal range. WBC and RBC did not change significantly but while RBC values for pre-treatment and post-treatment fell within normal range, only the WBC value of post-treatment did. Assay of FSH, progesterone, estrogen and prolactin revealed no significant (p . 0.05) difference between pre-treatment and post-treatment; however, noticeable higher pre-treatment LH concentration and elevated post-treatment testosterone concentration were observed. The work showed that Spondias mombin at 800mg/kgBW has profertility tendencies in the buck and can be considered as an aphrodisiac in goat breeding in developing countries probably at a higher dosage.